Comparison of quinine-doxycycline and quinine-clindamycin for falciparum malaria in children - Ditho Athos P. Daulay; Yunnie Trisnawati; Syamsidah Lubis; Munar Lubis; Syahril Pasaribu (Paediatrica Indonesiana, 2011)
Objective To compare the efficacy of quinine-doxycycline to quinine-clindamycin combination, as treatment for uncomplicated falciparum malaria in children.Methods This randomized open labelled controlled trial was conducted from July to August 2007 at Mandailing Natal, Sumatera Utara Province. The subjects were 8 – 18 year old children with positive Plasmodium falciparum from the peripheral blood smear. Simple randomization was performed to determine subject study into two groups of treatment, one group received quinine-clindamycin and the other received quinine-doxycycline treatment. The parasitemia was counted on day 0, 2, 7 and 28. We also observed the adverse effects of the antimalarial combination.Results Two hundred and forty six children who fulfilled the inclusion criteria were divided into two groups. All subjects completed the study. Cure rate achieved 100% from peripheral blood smear examination at the second day observation and showed no recrudescence at day 28th. (P=0.0001). During 28 days follow up, there were 21 (17.6%) patients suffered from headache, 18 (14.6%) vomit and 40 children (32.5%) suffered from tinnitus in quinine-doxycycline combination, compared to quinine-clindamycin combination group only 4 (3.3%) suffered from headache, 1 (0.8%) suffered from tinnitus and there was no vomiting experience in any patient (P < 0.0001).Conclusion Combination of quinine with either clindamycin or doxycycline are effective as an alternative antimalarial treatment. The combination of quinine-clindamycin is well tolerated than the combination of quinine-doxyciline, and this combination may be particular value for young children and pregnant women, as these two groups cannot receive doxycycline.